ACE and ACTN3 genotype in Korean power performance - Kim, C.; Kown, I.S.; Kim, H.J.; Cho, J.Y. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
There has been intensive research on the ACE ID or ACTN3 R577X polymorphism in the athletic trait of power performance due to the phenotypic influence of their genotypes on skeletal muscle power or muscle fiber structure(Hagberg et al. 2011). How ever, there is in need to identify the impact of combined association of ACE and ACTN3 on human performance because power performance is genetically determined by polygenic profiles(Rodriguez-Romo et al., 2010; Santiago et al., 2010). This study aimed to exam whether the combination of ACE and ACTN3 is associated with power performance in Korea. METHODS: For this study, 106 top-class power athletes (top-class group), 158 elite power athletes (elite-class group) and 676 healthy adults (control) aged 18-39 yrs were recruited and their genotypes were analyzed. RESULTS: The top-class group showed higher frequencies of II genotype and I allele in ACE and also higher frequencies of RR genotype and R allele in ACTN3 (Top-Class vs. Control: 41.4% vs. 32.1% for II genotype, 67.1% vs. 57.7% I allele, p<0.05; 42.3% vs. 29.0% for RR genotype, 65.3% vs. 54.8% for I allele, p<0.05). In polygenic profile, the top-class group had significantly higher freqencies of combined-II/ID+RR/RX genotype than control (Top-Class vs. Control: 82.9% vs. 66.7% for II/ID+RR/RX, p<0.05). The combined-II/ID+RR/RX genotype showed the possibility of succusse in the top-class muscle power performance with odds ratio of 2.3 times (CI:1.4-4.1, p<0.05). DISCUSSION: There results suggested that ACE and ACTN3 should be in interaction with each other to affect muscle-power performance in an additive form. Also, multigenic profile of ACE and ACTN3 can predict muscle performance with homogeneous dominant combined genotype (II/ID+RR/RX) having high success.